Keys to drawing - Dodson, Bert. (Cincinnati, Ohio : North Light Books, 1990)
Provides illustrated, step-by-step lessons that explore the fifty-five keys to drawing, covering proportion, light, depth, texture, design, and other topics.
Includes bibliographical references (p. 222) and index.
Adult
Adult
Keywords: Drawing -- Technique; Drawing -- Technique